Gambaran Karakteristik Anemia Pada Pasien Penyakit Ginjal Kronis Yang Dirawat Di RSUP Dr. Tadjuddin Chalid - Darmo, Lutfiany; Sartika, Suriana Dwi; Abrar, Hanan Khasyrawi (Fakultas Kedokteran Universitas Bosowa, 2025)
Chronic Kidney Disease is a kidney disease in which there is a decrease in kidney function over a period of months to years which is characterized by a slow decrease in the glomerular filtration rate (GFR) over a long period. 1 There are no initial symptoms of chronic kidney disease, however Over time, when chronic kidney disease worsens, symptoms will appear such as: swelling of the legs, fatigue, nausea and vomiting, loss of appetite, and confusion. Kidney function indicates the condition of the kidneys and their function in kidney physiology. A risk factor for chronic kidney disease can be the patient's family history of the disease. This research was conducted on 100 people with chronic kidney disease who experienced anemia who were hospitalized at Dr. Tadjuddin Chalid Hospital. This research used a descriptive observational method using secondary data in the form of medical records of chronic kidney disease sufferers who had anemia who were hospitalized at Dr. Tadjuddin Chalid Hospital. The results of this study show the distribution of chronic kidney disease sufferers who experience anemia who are hospitalized at Dr. Tadjuddin Chalid Hospital, namely: (1) Characteristics based on age are mostly late elderly (44%), (2) More often suffer from severe anemia (50%), (3) With the highest degree of GFR, namely at stage 5 (85%), (4) there is more history of hypertension (46%), history of diabetes mellitus (29%), history of urinary tract stones (6%), prostate hypertrophy (16%) and others ( 3%). Based on the results of research describing the characteristics of anemia in CKD patients who were hospitalized at Dr. Tadjuddin Chalid Hospital of 100 samples, it was found that patients in late elderly age were the majority of patients who experienced chronic kidney disease, had severe degrees of anemia and had GFR stage 5 and had the most comorbid diseases. Many are hypertension.